A microstrip bandpass filter based on inductive coupled quarter‐wavelength resonators. Issue 5 (23rd March 2013) - Cheng, Fei; Lin, Xianqi; Zhang, PengCheng; Song, Kaijun; Fan, Yong
Abstract This article proposes a compact filter using inductive coupled quarter‐wavelength resonators.The coupling between the quarter‐wavelength resonators is realized by a short‐end stub which behaves as a K‐inverter. As a result, the coupling coefficient of the resonators can be easily controlled by the length of the short‐end stub. A fourth‐order filter is designed and fabricated to demonstrate the proposed method. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1031–1033, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27469